Manipulation of hot carrier cooling dynamics in two-dimensional Dion–Jacobson hybrid perovskites via Rashba band splitting - Jun Yin (Nature Portfolio, 2021)
Hybrid perovskite is a promising class of material for optoelectronic applications due to the slow hot-carrier cooling, yet the process is not well-understood in material with Rashba band splitting. Here, the authors reveal spin-flipping and spin-dependent scattering of hot electrons are responsible for accelerating the cooling at longer delays.